Lymph node characteristics of 6279 N1 differentiated thyroid cancer patients. Issue 3 (March 2020) - Sui, C; He, Q; Du, R; Zhang, D; Li, F; Dionigi, G; Liang, N; Sun, H
Abstract : Purpose: This study examined the clinicopathological characteristics of 6279 N1 differentiated thyroid cancer (DTC) patients who underwent operations in our center. Methods: This was a retrospective longitudinal analysis. We categorized the DTC patients on the basis of various lymph node (LN) characteristics. Logistic regression models and multiple linear regression models were used for the correlation analysis. Results: A total of 3693 (58.8%) N1a patients and 2586 (41.2%) N1b patients were included. Patients with N1b disease had larger metastatic foci (0.5 vs 0.15 cm), a greater number of metastatic LNs (5 vs 2), a greater number of dissected LNs (25 vs 7), and a smaller lymph node ratio (NR, number of positive LNs/number of sampled LNs) (23.1% vs 28.6%) than patients in stage N1a. Comparing the clinicopathological features, we found that male, increased tumor size, multifocality, and thyroiditis increased the risk of stage N1b disease ( P < 0.05). Sex, multifocality, capsular infiltration, and tumor size were associated with the size of the metastatic LNs ( P < 0.05). Sex, capsular infiltration, and nodular goiter were associated with the NR ( P < 0.05). Female sex, tumor located in inferior lobe, maximal tumor diameter (MTD) < 1 cm, and nodular goiter were independent predictors for skip metastases ( P < 0.05). MTD > 1 cm, central neck metastasis and age were independent predictors for bilateral lateral neck metastasis (BLNM) ( P < 0.05). Conclusion: The LN characteristics of stage N1a and N1b disease were associated with significantly different features, such as sex, tumor size, multifocality, capsular infiltration, and nodular goiter.